EFFECT OF ETHANOLIC EXTRACT OF MELINJO PEEL (Gnetum gnemon) ON SERUM MALONDIALDEHYDE (MDA) LEVELS IN HYPERURISEMIA WISTAR STRAIN RATS - Indra Priawan; Yetty Machrina; Ririe Fachrina Malisie (JBIO: jurnal biosains (the journal of biosciences), 2022)
Hyperuricemia is a state of uric acid in the body that is higher than the body's tolerance limit. The formation of uric acid will be accompanied by the formation of Reactive Oxygen Species (ROS) by the changes of Xanthine Dehydrogenase to Xanthine Oxide with the help of NAD+ and Oxygen, which can trigger oxidative stress, causing cell damage and apoptotic cell, one of which is through lipid peroxidation followed by the release of Malondialdehyde (MDA) into the extracellular space. This study aims to analyze the effect of giving melinjo peel ethanol extract (Gnetum gnemon) on serum MDA levels in hyperuricemic Wistar strain rats. Rats were grouped into 4 treatment groups, namely K0 (without treatment), Kneg (hyperuricemia and CMC), Kpos (hyperuricemia and allopurinol), and P (hyperuricemia and ethanol extract of melinjo peel). Manufacture a hyperuricemic rat model by giving a high-fructose diet and then measuring uric acid levels to ensure that the rat is already in hyperuricemia. The high-fructose diet was continued until the rats were executed. Serum MDA was measured using the Thiobarbituric acid (TBA) method. The results showed differences in MDA levels between groups of hyperuricemic rats. Based on the examination of lower MDA levels after administration of melinjo peel ethanol extract compared to the CMC group and the allopurinol group, statistically significant differences were obtained (p = 0.001). Based on the analysis results, it was concluded that the ethanolic extract of melinjo peel (Gnetum gnemon) could reduce serum MDA levels in hyperuricemic Wistar rats.